2021
DOI: 10.1002/jlb.3ab0520-339rr
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-derived extracellular vesicles modulate the phenotype of naïve human neutrophils

Abstract: Neutrophils (PMN) regulate inflammation in many ways, including communication with other immune cells via extracellular vesicles (EVs). EVs released by human neutrophils activated with N‐formylmethionyl‐leucyl‐phenylalanine (fMLF) (PMN‐fMLF EVs) had an outside‐out orientation and contained functionally important neutrophil plasma membrane proteins, including flavocytochrome b558, and enzymatically active granule proteins, elastase, and myeloperoxidase. Treatment of naïve PMN with PMN‐fMLF EVs primed fMLF‐stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…The critical role of nEVs on naïve neutrophils may explain how acute local inflammation in a limited area can expand and become chronic. This point is illustrated by the recent work of Nauseef’s group [ 79 ], which demonstrated that the treatment of naïve neutrophils with EVs derived from fMLF-stimulated neutrophils primed NADPH oxidase activity. This is reflected by an increase in ROS production in response to a suboptimal concentration of fMLF.…”
Section: Nevs In Diseasesmentioning
confidence: 97%
“…The critical role of nEVs on naïve neutrophils may explain how acute local inflammation in a limited area can expand and become chronic. This point is illustrated by the recent work of Nauseef’s group [ 79 ], which demonstrated that the treatment of naïve neutrophils with EVs derived from fMLF-stimulated neutrophils primed NADPH oxidase activity. This is reflected by an increase in ROS production in response to a suboptimal concentration of fMLF.…”
Section: Nevs In Diseasesmentioning
confidence: 97%
“…Stimulation of neutrophils by opsonized particles induces the release of bacteriostatic EVs, which form large aggregates with bacteria 82 . Furthermore, EVs from neutrophils stimulated with N -formylmethionyl-leucyl-phenylalanine, a chemotactic factor produced by bacteria, prime resting naive neutrophils for NADPH oxidase activity and enhance their phagocytic capacity 83 . Upon non-lytic NETosis, which involves the expulsion of nuclear chromatin and granules, anucleated, membrane-enclosed large remnants of neutrophils (cytoplasts) are left behind.…”
Section: Antimicrobial Responsesmentioning
confidence: 99%
“…In fact, EVs can be generated from all of the cells present in the CF lung including, but not limited to the neutrophils and epithelial cells, such as macrophages, monocytes, T‐cells, as well as bacteria and fungus 42 . There have been recent studies that EVs from neutrophils can cause activation of other neutrophils, 43 and that EVs from S. aureus can down‐regulate the ability of neutrophils to kill bacterial pathogens 44 . EVs from CFTR‐mutated epithelial cells were able to activate neutrophils 45 and our study now documents communication in the other direction, that is, from neutrophils to epithelial cells.…”
Section: Resultsmentioning
confidence: 99%